Minibeam Spatially-Fractionated Radiation Therapy Is Superior to Uniform Dose Radiation Therapy for Abscopal Effect When Combined with PD-L1 Checkpoint Inhibitor Immunotherapy in a Dual Tumor Murine Mammary Carcinoma Model - Judith N. Rivera; Keith Laemont; Artak Tovmasyan; Stefan Stryker; Kenneth Young; Theresa Charity; Gregory M. Palmer; Sha Chang (Radiation)
Spatially fractionated radiation therapy (SFRT) has a long history of treating bulky and hypoxic tumors. Recent evidence suggests that, compared to conventional uniform dose radiation therapy, SFRT may utilize different mechanisms of tumor cell killing, potentially including bystander and immune-activating effects. The abscopal effect in radiation therapy refers to the control or even elimination of distant untreated tumors following the treatment of a primary tumor with radiation, a process believed to be immune-mediated. Such effects have been shown to be enhanced by immunotherapy, particularly immune checkpoint inhibition. In this manuscript, we explore the potential synergy of spatially fractionated radiation therapy, in the form of kV x-ray minibeam, combined with PD-L1 checkpoint inhibition in a murine mammary carcinoma model at conventional dose-rate. We found that minibeam of peak/valley doses of 50 Gy/3.7 Gy performed statistically equivalent but trending better than that of 100 Gy/7.4 Gy in its abscopal effect and so 50 Gy/3.7 Gy was selected for further studies. Our findings indicate that the abscopal effect is significantly greater in the minibeam plus anti-PD-L1 treated animals compared to those receiving uniform dose radiation therapy plus anti-PD-L1 (p = 0.04948). Immune cell profiling in the minibeam plus anti-PD-L1 group compared to uniform dose reveals a consistent trend towards greater immune cell infiltration in the primary tumor, as well as a higher percentage of CD8+ T cells, both systemically and at the abscopal tumor site.